APLIKASI MONITORING DAN MANAJEMEN LABORATORIUM KOMPUTER TEKNIK INFORMATIKA UIN ALAUDDIN MAKASSAR - Andi Jumardi; Ridwan Ridwan (Teknosains, 2015)
As the center of a practicum student majoring in informatics engineering, informatics engineering laboratory processing often face problems in conducting lab. Problems in the face as the students who do not disiplain in following lab and lab equipment often lost in the computer lab. Based on these issues, then the purpose of the preparation of this paper is to minimize the occurrence of it by restricting the access rights of students who go into the computer lab informatics techniques. To achieve these objectives, then the steps - steps that consist of this type of research, system design, implementation and testing of the system. The type of research is quantitative descriptive research that is research the facts systematically describe the condition of the object of study, while the design of the system using Delphi programming language with dbislam database. The method of black box testing method that focuses on the functional requirements of the software. With the application to be built, the head of the laboratory can be more easily monitor and supervise the lab activities. Attendance laboratory, assistants and students can be in monitoring every when the head of the laboratory computer.